1997
DOI: 10.1002/(sici)1097-0215(19970703)72:1<166::aid-ijc24>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Application of cytokine intervention for improved radio-antibody dose delivery

Abstract: The goal of our studies was to determine whether administration of IL-1/GM-CSF to mice could reduce radio-antibodyinduced myelosuppression and allow either dose escalation of radio-antibody using 131 The potential efficacy of radiolabeled antibodies as a cancer therapeutic is dependent on the maximal tolerated dose (MTD) that can be achieved and on the frequency at which doses can be administered. Two factors influencing both the MTD and the dose frequency are the radionuclide and the form of immunoglobulin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…In good accord with earlier observations with 131 I-iodinated IgG (e.g., Behr et al, 1997e;Blumenthal et al, 1997), the blood-based maximum tolerated red marrow dose was found to be at approximately 17 Gy for 131 I-17-1A. Depending on the fraction of 125 I being internalized into the bone marrow cells and the extent of photon contribution, blood doses range between 10 and 24 Gy for 125 I-CO17-1A, which is well in the same range.…”
Section: Discussionsupporting
confidence: 90%
“…In good accord with earlier observations with 131 I-iodinated IgG (e.g., Behr et al, 1997e;Blumenthal et al, 1997), the blood-based maximum tolerated red marrow dose was found to be at approximately 17 Gy for 131 I-17-1A. Depending on the fraction of 125 I being internalized into the bone marrow cells and the extent of photon contribution, blood doses range between 10 and 24 Gy for 125 I-CO17-1A, which is well in the same range.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that cytokines (IL‐1, GM‐CSF) can also be used for dose intensification of RAIT (Blumenthal et al 1997, Blumenthal et al 1999). The efficacy of this method of intervention is limited to alleviating hematopoietic damage but does not affect GI toxicity or any other normal tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…This could help to explain why substrate adhesion is influenced by SMFs. Once again, the use of different fields can give different results, as for example with the inhibition of fibroblast adhesion in the presence of 60 and 1000 Hz EMFs, and melanoma cell adhesion in the presence of an SMF using a 4.7-T superconducting magnetic resonance imaging (MRI) magnet (Blumenthal et al, 1997b;Short et al, 1992).…”
Section: Differentiationmentioning
confidence: 99%